Avaliação da proteína amastina de Leishmania sob a forma recombinante e de epítopo específico de células B para o diagnóstico sorológico diferencial da leishmaniose visceral - Danniele Luciana Vale (2019)
The diagnosis of visceral leishmaniasis (VL) presents problems due to the toxicity and/or high cost of drugs. In addition, no vaccine exists to protect against human disease. In this study, the antigenicity and immunogenicity of amastin protein were evaluated in L. infantum–infected dogs and humans. For the diagnosis, besides the recombinant protein, 1 linear B-cell epitope was synthetized and evaluated in serological assays. Results showed high sensitivity and specificity values to detect the disease when both antigens were employed against a canine and human serological panel. By contrast, when using rA2 and a soluble Leishmania antigenic preparation, sensitivity and specificity values proved to be lower. A preliminary immunogenicity study showed that the amastin protein induced high IFN-γ and low IL-10 production in stimulated PBMC derived from treated VL patients and healthy subjects, thus suggesting a potential use of this protein as an immunogen to protect against human disease.